The Profit Function Analysis Of Corn Farming In Bengkulu Province - Julia Tridamayanti Sayuti; Ketut Sukiyono; Irnad Irnad (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
This aim of the study was 1) Analyze the profit received by corn farmers in Bengkulu Province, 2) Analyze the factors that affect the profits of corn farmers in Bengkulu Province. The method used in this study are descriptive method, analysis of farm costs and analysis of the profit function of Cobb-Douglass Unit Output Price (CD UOP), then using Shazam version 10 to see the factors that affect corn farming profits. In this study the determination of the sample using the census method. The results of this study indicate that the average profit of corn farmers in Bengkulu Province is Rp. 4.495.218,99/UT or Rp. 5.736.938,55/ha. Factors that have a real negative effect on corn farming profits in Bengkulu Province are the price of liquid pesticides (HPC) and men's labor wages (UTKP), while factors that have a negative and unreal effect are the price of phonska fertilizer (HP). While the factor that has a positive effect on the profit of corn farming in Bengkulu Province is land area (LL). Keywords: Corn farming, profit function, cobb douglass